TELAAH KOMPARATIF KINERJA KEUANGAN BANK UMUM INDONESIA SEBELUM DAN SAAT COVID 19 - asbi amin; Astika Landang; Margareta Seltin Hama; Hermanus Tolin Edo; Beatrix Maila Tamur (AkMen JURNAL ILMIAH, 2022)
This study aims to determine the performance of Islamic banking and banking before and during the COVID-19 pandemic as measured by the capital adequacy ratio (CAR), Return on Assets (ROA), Net Interest Margin (NIM)/Net Operating Margin (NOM), Operating Costs Per Operating Income (BOPO) and Loan to Deposit Ratio (LDR)/ Financing to Deposit Ratio (FDR). This type of research is a comparative study through a literature study, so the object of this research is the banking statistics report issued by the OJK. where this study will compare the financial performance of conventional banks book II and Islamic banks book II before and during the covid-19 pandemic by using financial ratios as comparison indicators. The financial ratios used are the ratio of CAR, ROA, NIM/NOM, BOPO, LDR/FDR. The analytical method used is descriptive statistical analysis used in this study is the minimum value, maximum value, average (mean) and standard deviation. In addition, the inferential statistical analysis used in this study was the Wilcoxon signed rank test with the help of SPSS. The results showed that there were differences in the CAR, ROA, NIM, BOPO and LDR ratios in BUKU II conventional commercial banks before and during the Covid 19 pandemic. Meanwhile, the CAR and NOM ratios in BUKU II Islamic commercial banks did not show any differences before and during the Covid pandemic. 19.